Environmental impact on the use of diesel waste plastic oil nano-additive blends in a DI diesel engine. (21st November 2021) - Sachuthananthan, B.; Vinoth, R.; Reddy, D. Raghurami; Bandari, Vishnuvardhan; Anusha, P.
An attempt was made here to exhibit the extraction, characterisation and consumption of waste plastic oil (WPO) extracted through pyrolysis process of mixed plastic waste in single cylinder diesel engine. Fuel blends of 80% diesel, 20% WPO with various dosage of cerium oxide (CeO2 ) nano-additive namely 25 ppm, 50 ppm, 75 ppm and 100 ppm in terms of volume were prepared individually and tested in a CI engine for combustion, performance and emission studies. Results indicated that out of all the four blends, diesel WPO blended with 75 ppm CeO2 nano-additive exhibits an increase in 4.5% NOx emission, significant drop in CO, HC, smoke emissions with 1.7% rise in BTE and abatement in BSFC when compared to other blends.